Design, research, and production of gear wheels for mining machines - Ustynenko Oleksandr; Bondarenko Oleksiy; Klymenko Sergij; Riabchenko Sergij; Protasov Roman (MATEC Web of Conferences, 2023)
The current state of the Ukrainian fuel and energy complex requires a continuous increase in coal production. As part of concept implementation for the coal industry development now created and introduced into serial production a new generation of mining machines. The most loaded element of mining machine is its gear wheels of cutting part. Calculations for the strength and durability of gearings have been carried out. The modelling of the teeth stress-strain state by the finite element method has also been carried out. Works were carried out on the processing of parts of gearboxes of mining machines. Investigations of the processes of blade processing of gears and shafts of gearboxes of coal combines were carried out. The state of the surface layer, the quality and accuracy of processing these parts with a blade tool made of superhard materials are determined. Researches of grinding of an involute profile of gear wheels of gearboxes of mining machines are carried out. A study was made of the surface quality and accuracy of gears after grinding with special abrasive wheels. The influence of processing processes with a tool made of superhard materials on the strength and durability of gear drives of mining machines is determined.